2016
DOI: 10.1177/1060028016657553
|View full text |Cite
|
Sign up to set email alerts
|

Neuroleptic Malignant Syndrome

Abstract: NMS is a rare adverse drug reaction, with a complex pathophysiology and presentation. Timely diagnosis and discontinuation of antipsychotic therapy is the first-line treatment, followed by supportive care and pharmacotherapy. Antipsychotic rechallenge is often required and should be attempted only after a drug-free period and with a different agent, slowly titrated with close monitoring.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
58
0
18

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 88 publications
(76 citation statements)
references
References 47 publications
(73 reference statements)
0
58
0
18
Order By: Relevance
“…[20] In our case, dantrolene sodium was not effective to improve the patient's symptoms. Dantrolene has been routinely used for NMS treatment, [19] while dantrolene is not universally accepted as a treatment for NMS.…”
Section: Discussionmentioning
confidence: 64%
See 2 more Smart Citations
“…[20] In our case, dantrolene sodium was not effective to improve the patient's symptoms. Dantrolene has been routinely used for NMS treatment, [19] while dantrolene is not universally accepted as a treatment for NMS.…”
Section: Discussionmentioning
confidence: 64%
“…Dantrolene has been routinely used for NMS treatment, [19] while dantrolene is not universally accepted as a treatment for NMS. [20,21] If the patient is demonstrating mild to moderate symptoms of rigidity and fever, dantrolene may be effective earlier in NMS presentation. [20] In contrast, for severe cases, dantrolene used as monotherapy is not recommended for treating NMS and may actually be associated with an increase in mortality and hepatitis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been noted that dantrolene may be effective in treating hyperthermia from many causes unrelated to MH caused by anesthesia [12]. On the basis of the similarity between a variety of drug-induced hyperthermic syndromes and MH, dantrolene has been used to effectively treat several syndromes, such as the neuroleptic malignant syndrome, 3,4-methylenedioxy-methamphetamine toxicity, and hyperthermia related to the new onset of juvenile diabetes in adolescents [13][14][15]. …”
Section: Discussionmentioning
confidence: 99%
“…However, others have suggested that the choice of antipsychotic should be one with low D2 affinity. 11 It is important to wait for resolution of NMS before rechallenge with some suggesting a ‘washout’ period of 2 weeks. 11 It is also advisable to restart at a low dose and to monitor for re-emerging signs of NMS.…”
Section: Discussionmentioning
confidence: 99%